Peran dan Fungsi Komunikasi Keluarga dalam Adaptasi Pranata Keluarga Islami Di Tengah Pandemi Covid-19 - Robeet Thadi; Adisel Adisel; Depi Putri (JURNAL ILMIAH SYI'AR, 2021)
The intensity of communication between parents and children in the midst of the covid-19 pandemic is getting higher, the intensity of this communication will form a new cultural structure and culture in the family. This paper aims to explain how the role and function of family communication in the adaptation of Islamic family institutions. This research is a qualitative study, using library research as a data collection technique. That the family is indeed the smallest unit in society, but the family has a big role in successfully suppressing the impact of the covid-19 pandemic and success towards a new normal era. The function of family communication in the adaptation of Islamic family institutions in the midst of the covid-19 pandemic, through the functions of affective communication, socialization communication, and health care communication.